Vascularized Bone Grafting for the Treatment of Capitate Avascular Necrosis - Quintero, Jorge I.; Herrand, Maria C.; Moreno, Rodrigo (Journal of Wrist Surgery, 2021)
Avascular necrosis (AVN) of the capitate bone is a rare condition and it can be related to major trauma or idiopathy. Different treatments are available including soft tissue interposition and intercarpal arthrodesis including lunocapitate, scaphocapitate, four corner, and carpometacarpal fusions. Other surgical options are resection of the proximal pole and revascularization procedures. The main purpose of this article is to present two cases of AVN of the capitate treated with a revascularization procedure using the 4th–5th extensor compartment artery (4th–5th ECA). Two female patients with capitate AVN are reported with an average age of 30.5 years. Both cases were classified as type-I according to Milliez classification. The major complaint in each case was wrist pain that increased during activity. In both cases there was no history of trauma, smoking, diabetes, or hematologic diseases. Both patients had a diminished range of motion, grip, and strength. The definitive diagnosis was made with magnetic resonance imaging. Both patients underwent treatment revascularization of the capitate using a vascularized bone graft based on the 4th–5th ECA. At average follow-up of 12 months, each patient had improved with regards to pain and had increased grip strength. The literature does not describe a specific algorithm treatment for capitate AVN. We recommend revascularization of the capitate using the 4th–5th ECA in type-I Milliez classification in young patients without signs of carpal collapse.
Keywords: avascular necrosis; capitate; bone graft; carpal height; vascularized